Fodder shrubs: milking success - WRENmedia (WRENMedia, 2010)
In East Africa, Esther Karanja explains how opportunities for women have opened up following the introduction of low cost, easy to grow fodder trees for cattle feed, boosting milk yields and increasing household incomes by US$30-120 annually.